Dysregulation of microRNA biogenesis in cancer: the impact of mutant p53 on Drosha complex activity. Issue 1 (December 2016) - Gurtner, Aymone; Falcone, Emmanuela; Garibaldi, Francesca; Piaggio, Giulia
Abstract A widespread decrease of mature microRNAs is often observed in human malignancies giving them potential to act as tumor suppressors. Thus, microRNAs may be potential targets for cancer therapy. The global miRNA deregulation is often the result of defects in the miRNA biogenesis pathway, such as genomic mutation or aberrant expression/localization of enzymes and cofactors responsible of miRNA maturation. Alterations in the miRNA biogenesis machinery impact on the establishment and development of cancer programs. Accumulation of pri-microRNAs and corresponding depletion of mature microRNAs occurs in human cancers compared to normal tissues, strongly indicating an impairment of crucial steps in microRNA biogenesis. In agreement, inhibition of microRNA biogenesis, by depletion of Dicer1 and Drosha, tends to enhance tumorigenesis in vivo. The p53 tumor suppressor gene, TP53, is mutated in half of human tumors resulting in an oncogene with Gain-Of-Function activities. In this review we discuss recent studies that have underlined a role of mutant p53 (mutp53) on the global regulation of miRNA biogenesis in cancer. In particular we describe how a new transcriptionally independent function of mutant p53 in miRNA maturation, through a mechanism by which this oncogene is able to interfere with the Drosha processing machinery, generally inhibits miRNA processing in cancer and consequently impacts on carcinogenesis.